CEO curiosity and firm innovation - YU, Hui (Institutional Knowledge at Singapore Management University, 2021)
As an important personality trait, CEO curiosity is emphasized in practice but obtains little attention in theory. This dissertation aims to investigate the impact of CEO curiosity on firm innovation and the mediating role of external search. I argue that both diversive and specific curiosity of CEOs are positively correlated to firm innovation based on upper echelons theory (UET). Furthermore, search breadth mediates the positive connection between CEO diversive curiosity and firm innovation, while search depth mediates the positive connection between CEO specific curiosity and firm innovation. Besides, I explore the moderating effects of firm performance and market competition on the correlation between CEO curiosity and external search. Using survey data, I obtain strong empirical support for the theoretical model. This dissertation strives to investigate the connection between CEO curiosity and firm innovation, tackle the mechanism behind the relationship, and enrich the research of the upper echelons theory.